2007
DOI: 10.1097/fjc.0b013e31802d0001
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Increase in Flow-Mediated Dilation After Daily Intake of High-Flavanol Cocoa Drink Over 1 Week

Abstract: A single-dose ingestion of flavanol-rich cocoa acutely reverses endothelial dysfunction. To investigate the time course of endothelial function during daily consumption of high-flavanol cocoa, we determined flow-mediated dilation (FMD) acutely (for up to 6 hours after single-dose ingestion) and chronically (administration for 7 days). The study population represented individuals with smoking-related endothelial dysfunction; in addition to FMD, plasma nitrite and nitrate were measured. The daily consumption of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
129
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(142 citation statements)
references
References 36 publications
12
129
1
Order By: Relevance
“…However, it is possible that cocoa increased antioxidant potential and thus increased NO bioavailability independent of changes in oxidized LDL. Also of importance is our observation that vascular responses to nitroglycerin were similar after cocoa ingestion (0 -26 g cocoa) on all study days, consistent with prior findings (1,20,44). Collectively, these findings suggest that cocoa-induced increases in brachial artery FMD are likely to be mediated by enhanced production rather than enhanced vascular responsiveness to NO.…”
Section: Variablesupporting
confidence: 79%
“…However, it is possible that cocoa increased antioxidant potential and thus increased NO bioavailability independent of changes in oxidized LDL. Also of importance is our observation that vascular responses to nitroglycerin were similar after cocoa ingestion (0 -26 g cocoa) on all study days, consistent with prior findings (1,20,44). Collectively, these findings suggest that cocoa-induced increases in brachial artery FMD are likely to be mediated by enhanced production rather than enhanced vascular responsiveness to NO.…”
Section: Variablesupporting
confidence: 79%
“…An increase in arterial dilatation, determined from changes in digital pulse wave amplitude following forearm occlusion has been demonstrated previously in healthy adults after consuming 851 mg cocoa flavanols per day for 5 days. 2 Recently Heiss et al 3 also reported an increase in arterial dilatation, assessed by FMD, in a group of smokers following 7 days of consuming 918 mg per day of cocoa flavanols. While these studies provide clear evidence of an effect of short-term consumption of cocoa flavanols on endothelial function, the lack of placebo control prevents a definitive interpretation of the results as being directly caused by the cocoa flavanols.…”
Section: Discussionmentioning
confidence: 96%
“…In recent years, the consumption of cocoa products containing flavanols and procyanidins (oligomeric flavanols) has been shown to elicit dosedependent acute improvements in FMD, and regular consumption for up to 14 days provides a sustained improvement in FMD. [2][3][4][5] Improvements in FMD are associated with increased skeletal muscle blood flow during exercise, 6 suggesting that improvements in FMD might facilitate increased blood flow and nutrient delivery to sites of metabolism, particularly skeletal muscle during exercise, with resultant improvements in metabolic control and body composition. Indirect support for this hypothesis comes from studies that have shown that the consumption of flavanol-containing cocoa products, and L-arginine (the primary substrate for NO), not only improve FMD, 7 but also reduce body fat.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid elimination of catechins proposed to explain the lack of observed effects of the HP apple on FMD could not hold for phenolic acids, which would therefore be truly inactive. Another FMD study with a cocoa drink, regularly consumed over 1 week and providing about 900 mg flavanols per day, showed an increase in FMD building up over the week, but FMD measurement was carried out 2 h after consumption of the cocoa drink (Heiss et al, 2007). Two long-term studies have been carried out with flavanol-rich cocoa.…”
Section: Polyphenol-rich Apple and Endothelial Function S Auclair Et Almentioning
confidence: 99%